A DATA DISSEMINATION MODEL FOR VEHICULAR ADHOC NETWORK (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Vehicular adhoc network (VANET) is an emerging network which is depend on the communication of data through vehicular network via data pushing. Data pushing in between the vehicles was done by the data pushing communication model. In this paper, we present a formal model of data dissemination in between the vehicles by the mobility of vehicles and describe also the affects of data dissemination and study their characteristics which define the mobility if data dissemination in bidirectional mobility, we also study the data push model in the context of Traffic View, a system that we have implemented to disseminate information about the vehicles on the road. Traffic data could be disseminated using the cars moving on the same direction, cars moving in the opposite direction, or cars moving in both directions.